1999
DOI: 10.1007/s000180050487
|View full text |Cite
|
Sign up to set email alerts
|

Insights from von Willebrand disease animal models

Abstract: von Willebrand disease is a genetic bleeding disorder that arises from abnormalities in von Willebrand factor, an adhesive glycoprotein involved in both primary hemostasis and coagulation. It is the most common inherited bleeding disorder in humans, and over the years several animal species have also been described as suffering from this disease whether through a spontaneous mutation (pigs, dogs) or a genetically engineered one (mouse). These different animal models are extremely useful in exploring the charac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
29
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 111 publications
0
29
0
Order By: Relevance
“…Whether the VWF is necessary for ␣-granule storage needs to be tested in the future by crossing these animals onto a vWF null background. 40 We had postulated that the reason megakaryocytes stored ectopically expressed uPA was because these cells express a uPA receptor. 39 Thus, it may be fortuitous that the first 2 ectopically expressed proteins in megakaryocytes are stored in the platelets as both have a carrier protein that is naturally targeted to the ␣-granules.…”
Section: Discussionmentioning
confidence: 99%
“…Whether the VWF is necessary for ␣-granule storage needs to be tested in the future by crossing these animals onto a vWF null background. 40 We had postulated that the reason megakaryocytes stored ectopically expressed uPA was because these cells express a uPA receptor. 39 Thus, it may be fortuitous that the first 2 ectopically expressed proteins in megakaryocytes are stored in the platelets as both have a carrier protein that is naturally targeted to the ␣-granules.…”
Section: Discussionmentioning
confidence: 99%
“…While canine hemophilia and von Willebrand disease are common, a variety of clotting factor deficiencies and platelet function defects caused by surface glycoprotein abnormalities, storage pool defects, and failure of signal transduction occur in this species. [44][45][46] Comprehensive testing of the GSDs described in this report revealed a new canine hemostatic defect with features comparable to Scott syndrome of human beings. The affected dogs experienced a mild to moderate bleeding tendency but had normal in vitro coagulation and normal response to tests of platelet adhesion, aggregation, and secretion.…”
Section: Discussionmentioning
confidence: 99%
“…The importance of VWF for the hemostatic system is illustrated by the severe bleeding tendency associated with its functional deficiency, both in patients and in animal models. 10,11 Interestingly, studies using VWF-deficient mice revealed that VWF might also participate in inflammatory processes. For instance, when VWF Ϫ/Ϫ mice were stimulated in a cytokine-induced meningitis model (which represents a model for acute inflammation), reduced neutrophil infiltration compared with control mice was observed.…”
Section: Introductionmentioning
confidence: 99%